CONSUMER IMPULSIVE BUYING BEHAVIOR OF SERVICES SECTOR IN JORDAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This study aimed at a statement The Relationship between Factors Affecting Consumers to Impulsive Buying Behavior and the Jordanian Telecommunications Sector to achieve the aim of the study, the researchers reviewed the literature that dealt with the relationship of factors affecting impulsive buying behavior among customers in the communications sector. To achieve the goal of the study will compare the results of these studies, the researchers also noted that most of the previous studies focused on the perspective of the impact of personal factors and store factors in the measurement of impulsive buying behaviors in general and for telecommunications companies in particular. Moreover, personal factors along-with social factors are the most influential mechanism that deeply influences the consumer’s behavior. Especially these factors have strong significant influence and work hand in hand in Jordanian telecom sector The researchers also recommended It is necessary to focus telecommunications companies on personal factors that include matters specific to customers to focus on how to target and satisfy them in addition to taking into account the demographic factors that alerting these companies to diversify the services provided in order to target and satisfy a large segment of customers and do not forget the store factors that express The exhibition environment so that the environment for these exhibitions is designed and provided with services that can be in line with the aspirations of customers this relevant recommendation regarding impulse buying behavior, aimed at indicating ways in which the Jordanian telecom sector can raise its competitive advantage and regulatory performance in Jordan.